A Debreceni Tudományegyetem Orvostudományi Karának tansegédszemélyzete 1919–1950 II. rész: Klinikák - Mudrák, József (Gerundium, 2011)
The Assista nt Personnel of the Medical School of the University of Debrecen, 1919–1950. Part 2: The Clinics/1. Indispensable participants of the teaching and therapeutic activities of the Medical School of the University of Debrecen were the personnel assisting the work of the professors. The register is designed to serve as an overall recording of the pertinent data of the departmental professors, assistant professors, instructors, interns, and teaching assistants. In this second part the assistant personnel of the following clinics is registered: Clinic of Neurology and Psychiatry, Clinic of Ophthalmology, Clinic of Pediatry, Clinic of Dermatology and Sexual Pathology, Clinic of Obstetrics and Gynaecology. II.